The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1159/000506201
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Vessels Enhancing Adaptive Immunity Deteriorates Renal Inflammation and Renal Fibrosis

Abstract: Background: Lymphatic vessels transport lymph away from microvascular beds into the cardiovascular system. The basic function of the lymphatic system include absorption of wa ter and macromolecules in the interstitial fluid, which plays an important role in maintaining osmotic balance of the body. Recent studies have shown that lymphangiogenesis is associated with tumor metabolism, injury repair, and chron ic inflammation, and deteriorates disease progression via immune cell trafficking. Summary: Renal interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…However, this study revealed that lymphangiogenesis exacerbated UUO-induced contralateral intrarenal inflammation and subsequent fibrosis, and eplerenone inhibited lymphangiogenesis and alleviated renal injury. These findings are consistent with those studies of lymphangiogenesis in other CKDs, such as lupus nephritis, antineutrophil cytoplasmic antibody-associated nephritis, tubulointerstitial nephritis, focal segmental glomerulosclerosis, crescentic nephritis, type II diabetic nephropathy, and IgA nephropathy, which exhibit significantly increased lymphangiogenesis compared with controls 4 , 19 , 20 . During chronic inflammation, lymphangiogenesis is a kind of disorderly expansion that can hinder the clearance of immune cells, leading to the accumulation of macrophages, dendritic cells, T and B lymphocytes, and fibroblasts, thereby exacerbating the chronic inflammatory response and ultimately leading to fibrosis 21 .…”
Section: Discussionsupporting
confidence: 92%
“…However, this study revealed that lymphangiogenesis exacerbated UUO-induced contralateral intrarenal inflammation and subsequent fibrosis, and eplerenone inhibited lymphangiogenesis and alleviated renal injury. These findings are consistent with those studies of lymphangiogenesis in other CKDs, such as lupus nephritis, antineutrophil cytoplasmic antibody-associated nephritis, tubulointerstitial nephritis, focal segmental glomerulosclerosis, crescentic nephritis, type II diabetic nephropathy, and IgA nephropathy, which exhibit significantly increased lymphangiogenesis compared with controls 4 , 19 , 20 . During chronic inflammation, lymphangiogenesis is a kind of disorderly expansion that can hinder the clearance of immune cells, leading to the accumulation of macrophages, dendritic cells, T and B lymphocytes, and fibroblasts, thereby exacerbating the chronic inflammatory response and ultimately leading to fibrosis 21 .…”
Section: Discussionsupporting
confidence: 92%
“…This initial phase of antigen presentation T cell activation is followed by a period of immune response integration [22], The effector phase that follows is Humoral factors released by infiltrating and residual renal cells act as mediators. Bidirectional communication between enlisted invading inflammatory cells and renal parenchyma, either via direct contact or via local soluble cytokines, eventually regulates The progression and severity of renal contribution [23].…”
Section: Discussionmentioning
confidence: 99%
“…Organ lymphatic vessels can reabsorb tissue fluid back to the circulatory system to maintain tissue environmental homeostasis. In addition to tumors [ 1 , 2 , 3 ], organ transplantation [ 4 ], inflammation [ 5 , 6 ], and wound healing [ 7 ], the role of lymphangiogenesis in organ fibrosis has gradually attracted attention in recent years, such as in renal fibrosis [ 6 , 8 , 9 , 10 , 11 ], liver fibrosis [ 12 , 13 ], cardiac fibrosis [ 14 , 15 , 16 , 17 ], pulmonary fibrosis [ 18 , 19 , 20 , 21 ], tumor fibrosis [ 22 ] and peritoneal fibrosis [ 23 , 24 ]. Increasing evidence suggests that lymphangiogenesis is related to the onset and progression of fibrotic disease, and VEGFC/VEGFR3 is central in lymphangiogenesis.…”
Section: Introductionmentioning
confidence: 99%